Kearifan Lokal Baduy Banten - Amirullah Syarbini (Refleksi: Jurnal Kajian Agama dan Filsafat, 2015)
Baduy, a group of people and a tribe in Indonesia, still haveconserved their local wisdom. They live in Lebak, Banten. Their ultimatevalues are to reserve the universe without changing, moreover destroying, it;never to rebel but to feel satisfied with their modest life; to cooperate to dosomething and to help one another; to have discussion to solve their dailyproblems; to spend the time for working hard in fulfilling their needs; neverto annoy the others or even to suffer the others. These all characters are based on their custom, which they have kept from thousand of years. They are really sincere to accept their tribal tasks with all the consequences.